The fruit flies (Diptera: Tephritidae) described by Theodor Becker from Iran and Western China revisited in the collections of the Zoological Institute, Saint-Petersburg and Museum für Naturkunde, Berlin - Korneyev, Severyn V.; Korneyev, Valery A. (Zootaxa, 2017)
The type specimens of fruit flies described by Dr. Theodor Becker based on material collected in China (Xinjiang and Xizang) and Iran by Russian expeditions directed by Petr Kozlov and Mykola Zarudny are listed and figured. They are deposited in the collection of the Zoological Institute of Russian Academy of Sciences, Saint Petersburg with some duplicates in the Museum für Naturkunde, Berlin. Current concepts of the species, their morphological characters (illustrated by photographs of type specimens), current condition, and nomenclature are discussed.